'I'm happy, and I'm passing. That's all that matters!': exploring discourses of university academic success through linguistic analysis. (4th July 2019) - Delahunty, Janine; O'Shea, Sarah
Abstract: 'Student success' is a key driver in higher education policy and funding. Institutions often adopt a particular lens of success, emphasising 'retention and completion', 'high grades', 'employability after graduation' discourses, which place high value on human capital or fiscal outcomes. We explored how students themselves articulated notions of success to understand how these meanings aligned with the implicit value system perpetuated by neoliberal higher education systems. Qualitative data collected from 240 survey responses in the first phase of a study, were analysed usingAppraisal, a linguistic framework to systematically categorise evaluative language choices. This article focuses on questions eliciting students' articulations of success. Neoliberal discourses were challenged by these students, who were first-in-family at university, with success expressed in a personal and generational sense rather than solely meritocratic terms.